BADAN LEGISLASI DEWAN PERWAKILAN RAKYAT REPUBLIK INDONESIA SEBAGAI PENYELENGGARA PERCEPATAN DAN PEMBENTUKAN UNDANG-UNDANG DI INDONESIA - Ridha Putri Thaibah; Maria Maya Lestari; Zulwisman Zulwisman (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2023)
Article 1 point 1 of Law Number 12 of 2011 concerning the Establishment ofLegislation, states that the Formation of laws and regulations is the making of Legislationstarting from the stages of planning, drafting, discussing, validating or stipulating, andenacting. One of the most crucial stages in the formation of a law is the planning stage. Theconcept of planning for the formation of laws so far has been implemented through theNational Legislation Program (Prolegnas) as the only law planning instrument that is set inthe medium term (five years) and annually (one year) and based on a priority scale. Thedelay in establishing the National Legislation Program is a form of non-compliance by thestakeholders in charge of forming the law. And the Legislative Body of the DPR RI as one ofthe complementary tools of the DPR which assists in planning the formation of laws has agreat responsibility for the preparation and coordination of the Prolegnas.The purpose of this study is to find out how the role of the DPR Legislative Body is inthe process of forming laws and what is the ideal concept of the DPR Legislative Body as anorganizer of the process of accelerating the formation of laws in Indonesia. This research isnormative juridical research and is supported by empirical data, research conducted basedon legislation and additional interview data. The approach taken includes a libraryapproach, namely by studying books and laws and regulations and an interview approachwith informants. The type of data used is premier data type, namely data sources obtainedthrough interviews with sources related to the Legislative Body, secondary data sources,namely data sources derived from books and other regulations, which consist of premierlegal materials, secondary legal materials and legal materials. tertiary law.The Legislative Body of the DPR RI as a complementary organ for the council incarrying out its duties in the process of forming laws has a fairly important role in theprocess of planning the formation of laws. And in carrying out its duties, the Legislative Bodyhas constraints and problems that interfere with the Legislation Body's duties. It is necessaryfor every member of the DPR Legislative Body to understand the duties or responsibilities ofthe Legislative Body as a complementary tool for the DPR in implementing the legislativefunction in the process of accelerating the formation of laws in Indonesia in order to achievethe goal of developing national law.Keywords : Legislation Body, National Legislation Program, Law Number 12 of 2011Concerning the Formation of Legislation